Composition and resistance heating body

By using Ru-Mo-W alloy as the material of the resistance heating body, the problem of insufficient balance in the durability, resistivity temperature dependence and processability of the resistance heating body in the prior art is solved, and better resistance heating is achieved Performance and processability.

CN119452112APending Publication Date: 2025-02-14TOHOKU UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380044265.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-25
Filing Date
2023-10-23
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing metal resistance heating bodies are not balanced in terms of high durability, temperature dependence of resistivity and processability at room temperature, making it difficult to meet commercial needs.

Method used

Ru-Mo-W alloy is used as the material for the resistance heating body. The chemical composition of the alloy is calculated as atomic %: Mo exceeds 0% and is less than 49%, W exceeds 0% and is less than 45%, Mo content and W content The sum is more than 30% and less than 50%. The alloy can be powdery or mixed with solvent into a paste, and is suitable for thin films and linear or rod-shaped resistive heating bodies.

Benefits of technology

Ru-Mo-W alloy resistance heating body exhibits good balance characteristics in terms of durability, resistivity and temperature dependence, and has excellent processability at room temperature, and is suitable for various high-temperature heating devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119452112A_ABST
    Figure CN119452112A_ABST
Patent Text Reader

Abstract

The present invention provides a composition containing a Ru-Mo-W alloy having a chemical composition in which, in atomic%, Mo is more than 0% and 49% or less, W is more than 0% and 45% or less, and the sum of the Mo content and the W content in the Ru-Mo-W alloy is more than 30% and less than 50%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composition and a resistance heating element. This application claims priority based on Japanese Patent Application No. 2022-134489 filed in Japan on August 25, 2022, the contents of which are incorporated herein by reference. Background Art

[0002] In a resistance heating furnace, a resistance heating element disposed in the furnace is heated by applying direct current or alternating current to the resistance heating element so as to generate heat. As for the material of the resistance heating element, there are known carbon-based materials such as carbon (C) or silicon carbide (SiC), ceramic materials such as zirconium oxide (ZrO2) or lanthanum chromate (LaCrO3), and metal-based materials such as tungsten (W) or tantalum (Ta).

[0003] The materials that can be used for the resistance heating element are mainly determined by the atmosphere required for heating and the target temperature. For example, the evaporation unit used for film formation of organic light emitting diodes (OLEDs) is a type of resistance heating furnace, and the evaporation unit is usually kept in a high vacuum (10 -5 Pa or so). In vacuum evaporation using an evaporation unit, a crucible-shaped container is arranged in an area surrounded by a resistance heating body, and the evaporation raw material is filled into the container. The furnace is heated by energizing the resistance heating body to dissolve the evaporation raw material. The atoms or molecules detached from the surface of the dissolved evaporation raw material are given directionality by the evaporation unit, and film formation is performed by adhering to a substrate arranged above the evaporation unit. Here, it is required that less substances other than the evaporation raw material are detached from the inside of the evaporation unit during film formation, so the resistance heating body that can be used in the evaporation unit is limited to substances with low volatility in high temperature and high vacuum. For a long time, for the resistance heating body used under high temperature and high vacuum conditions, for example, high melting point metals such as tungsten, molybdenum or tantalum with high melting point and low vapor pressure can be used. In particular, tantalum is different from tungsten or molybdenum. Because it has high ductility, it is easy to process into the desired resistance heating body shape even at room temperature. When used as a heating wire, it is widely commercialized due to its high degree of design freedom. Furthermore, since tantalum has a higher resistivity than tungsten or molybdenum, it can be heated by a lower current when heating a resistance heating body of the same volume, so it has the advantage of being able to miniaturize the current source or wires. As such tantalum wire, for example, tantalum wire manufactured by Nilaco Co., Ltd. can be cited (see non-patent document 1).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2005-281767

[0007] Non-patent literature

[0008] Non-patent literature 1: Internet <URL:https: / / shop.nilaco.jp / jp / estimates / ?MENU=15&FROM=14&large_category=1&middle_category=%E3%82%BF%E3%83%B3%E3%82%BF%E3%83%AB&small_category=%E7%B7%9A>

[0009] Non-patent document 2: DW Rhys, The fabrication and properties of ruthenium, J. Less-Common Met. 1 (1959) 269-291.

[0010] Non-patent document 3: AS Darling, Some Properties and Applications of the Platinum-Group Metals, Int. Metall. Rev. 18 (1973) 91-122. Summary of the invention

[0011] Problems to be solved by the invention

[0012] However, the durability temperature of the resistance heating element of tantalum is about 1600° C., which is lower than the durability temperature of the resistance heating element of tungsten or molybdenum.

[0013] In addition, the resistivity of metals generally increases as the temperature rises, but the temperature dependence of the resistivity of tantalum is greater than that of tungsten or molybdenum, and even a slight temperature change will cause a change in the resistivity, so the temperature controllability based on the control voltage or current is low. Furthermore, since the resistivity of tantalum is small at a lower temperature, there is a problem of a slower heating rate.

[0014] On the other hand, although the durability temperature of tungsten or molybdenum resistance heaters is higher than that of tantalum resistance heaters, they are difficult to process at room temperature. Therefore, in order to manufacture the resistance heater, tungsten or molybdenum needs to be heated, which increases the manufacturing cost.

[0015] As described above, conventional metal resistance heaters cannot satisfy the requirements necessary for commercialization, such as high durability, temperature dependence of resistivity, and processability at room temperature, in a well-balanced manner.

[0016] The present invention has been made in view of the above circumstances, and an object thereof is to provide a composition and a resistance heater that satisfy the requirements of durability, resistivity, temperature dependence of resistivity, and processability at room temperature in a well-balanced manner.

[0017] Technical means to solve problems

[0018] The gist of the present invention is as follows.

[0019] [1] A composition according to one embodiment of the present invention contains a Ru-Mo-W alloy, wherein the chemical composition of the Ru-Mo-W alloy is, in terms of atomic %, Mo exceeding 0% and not more than 49%, W exceeding 0% and not more than 45%, and the total of the Mo content and the W content in the Ru-Mo-W alloy exceeding 30% and not more than 50%.

[0020] [2] The composition according to [1] above, wherein the chemical composition of the Ru—Mo—W alloy contains, in atomic %, 10% to 40% Mo and 10% to 40% W, and the total of the Mo content and the W content in the Ru—Mo—W alloy may be 20% to 47%.

[0021] [3] The composition according to [1] or [2] above, wherein the Ru—Mo—W alloy may be in a powdery form or in a paste form mixed with at least a solvent.

[0022] [4] The composition according to [1] or [2] above, which may be a film.

[0023] [5] Another embodiment of the present invention relates to a resistance heating body containing a Ru-Mo-W alloy, wherein the chemical composition of the Ru-Mo-W alloy is as follows, in terms of atomic %: Mo is greater than 0% and less than 49%, W is greater than 0% and less than 45%, and the total of the Mo content and the W content is less than 50%.

[0024] [6] The resistance heating body according to the above [5], wherein the chemical composition of the above Ru-Mo-W alloy contains, in atomic %, Mo of 10% or more and 40% or less, and W of 10% or more and 40% or less, and the sum of the Mo content and the W content in the above Ru-Mo-W alloy can be 20% or more and 47% or less.

[0025] [7] The resistance heating element according to [5] or [6] above may have a breaking elongation of 5% or more in a uniaxial tensile test at room temperature.

[0026] [8] The resistance heating element according to [7] above may be in the shape of a wire or a rod.

[0027] Effects of the Invention

[0028] According to the present invention, it is possible to provide a composition and a resistance heating element that satisfy the requirements of durability, resistivity, temperature dependence of resistivity, and processability at room temperature in a well-balanced manner. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 1 is a contour diagram showing the resistivity corresponding to the chemical composition of the Ru—Mo—W alloy at 25° C. in Example 1.

[0030] Figure 2 This is a graph showing the relationship between the Mo content and the W content relative to Ru in Example 1 and the resistivity.

[0031] Figure 3 This is a structural diagram showing the structure of a resistance heating body manufacturing apparatus that can be used to manufacture the resistance heating body according to one embodiment of the present invention.

[0032] Figure 4 This is a structural diagram showing a part of the structure of a resistance heating body manufacturing apparatus that can be used to manufacture the resistance heating body involved in the same embodiment.

[0033] Figure 5 This is a graph showing the temperature dependency of the resistivity in Example 2.

[0034] Figure 6 This is a graph showing the temperature dependency of the emissivity in Example 3.

[0035] Figure 7 These are images of each sample in Example 4 obtained by SEM-EBSD analysis.

[0036] Figure 8 : is the stress-strain curve of each sample in Example 4. DETAILED DESCRIPTION

[0037] Hereinafter, a composition and a resistance heating element according to an embodiment of the present invention will be described with reference to the drawings. It should be noted that the present invention is not limited to the following embodiments.

[0038] <Composition>

[0039] First, a composition according to an embodiment of the present invention is described. The composition according to the present embodiment contains a Ru-Mo-W alloy, and the chemical composition of the Ru-Mo-W alloy includes, in terms of atomic %, more than 0% and less than 49% of Mo, more than 0% and less than 45% of W, and the remainder is Ru and impurities, and the sum of the Mo content and the W content in the Ru-Mo-W alloy is more than 30% and less than 50%. The following is a detailed description. It should be noted that in the following description of the chemical composition, unless otherwise specified, the expression "%" means "atomic %". In addition, the content of each element is the content relative to the Ru-Mo-W alloy.

[0040] (Ru-Mo-W alloy)

[0041] The Ru—Mo—W alloy in the composition according to the present embodiment contains ruthenium (Ru), tungsten (W), and molybdenum (Mo).

[0042] Ru is one of the platinum group elements, has a high melting point (about 2334°C), excellent chemical stability, and low vapor pressure in a vacuum atmosphere. Ru has a hexagonal close-packed (HCP) structure and forms a Ru alloy by solid solution with other elements. The Ru-Mo-W alloy in the composition of this embodiment has Ru as the main component.

[0043] The resistivity of Ru as a single substance is as low as that of other pure metals. However, the resistivity changes when Ru contains alloy elements. The resistivity increases as the amount of alloy elements contained in Ru increases. Figure 2 As shown, when the resistivity of the Ru alloy is the vertical axis and the content of the alloying elements is the horizontal axis, when the Mo content in the Ru-Mo alloy and the W content in the Ru-W alloy are respectively below 40 atomic %, the resistivity increases with the increase of the Mo content and the W content.

[0044] On the other hand, according to the alloying elements contained, a fixed ratio compound is formed. For example, in the case of forming a fixed ratio compound such as an intermetallic compound, the metal structure of the Ru alloy becomes a complex phase structure, and the resistivity of the Ru alloy changes according to the form of the intermetallic compound as the precipitation phase. Moreover, since it is also difficult to control the form of the intermetallic compound, it is difficult to control the resistivity of the Ru alloy with a complex phase structure. Therefore, as a material for a resistance heating body, a metal material with a complex phase structure is usually not preferred. However, in the case where the precipitation phase is dissolved by heat treatment, it is not limited to this. In the case of solid solution with alloying elements, the resistivity becomes a value corresponding to the content of the alloying elements. Therefore, from the viewpoint of increasing the resistivity of the Ru alloy and thus increasing the resistivity of the composition, it is preferred to contain an element with a higher solid solubility for Ru and a higher degree of increase in the resistivity per unit concentration of the alloying element. In addition, from the viewpoint of use at high temperatures, it is preferred that the melting point of the Ru alloy is higher, for example, it is desired that the solidus temperature of the Ru alloy exceeds 1600°C. If the solidus temperature of the Ru alloy exceeds 1600° C., the Ru alloy can be used, for example, as a composition constituting a vapor deposition unit in the production of an organic EL material.

[0045] In addition, from the viewpoint of vapor pressure, it is desirable that the alloy element has a vapor pressure which is equal to or lower than that of Ru.

[0046] [Mo: more than 0% and 49% or less]

[0047] Mo has a high melting point (2623°C), is chemically stable, and has a low vapor pressure. If the Mo content is 49% or less, the melting point and resistivity of the Ru-Mo-W alloy can be increased. Mo is solid-dissolved in Ru at a maximum of about 40%. Mo above this amount sometimes forms intermetallic compounds such as σ phase. If the Mo content is 49% or less, the σ phase disappears by heating. On the other hand, if the Mo content exceeds 49%, the formed intermetallic compounds cannot be eliminated by heat treatment, and the metal structure of the Ru-Mo-W alloy cannot be formed into a single phase. Therefore, if the Mo content is 49% or less, the melting point and resistivity of the Ru-Mo-W alloy increase, and the reduction in processability can be suppressed. As a result, the resistivity of the composition increases, and the reduction in processability can be suppressed. Furthermore, if the Mo content is 40% or less, the generation of intermetallic compounds can be suppressed, so that a higher resistivity can be maintained and excellent processability can be maintained. Therefore, the Mo content is preferably 40% or less. On the other hand, the lower limit of the Mo content is not particularly limited, but in order to obtain the effect of increasing the melting point and the effect of increasing the resistivity by Mo, the Mo content is preferably 10% or more, and more preferably 13% or more.

[0048] [W: more than 0% and less than 45%]

[0049] W has a high melting point (3442°C), is chemically stable, and has a low vapor pressure. If the W content is 45% or less, the melting point and resistivity of the Ru-Mo-W alloy can be increased. W is solid-dissolved in Ru at a maximum of about 40%. W above this amount sometimes forms intermetallic compounds such as σ phase. If the W content is 45% or less, the σ phase disappears by heating. On the other hand, if the W content exceeds 45%, the formed intermetallic compounds cannot be eliminated by heat treatment, and the metal structure of the Ru-Mo-W alloy cannot be formed into a single phase. Therefore, if the W content is 45% or less, the melting point and resistivity of the composition increase, and the reduction in processability can be suppressed. Furthermore, if the W content is 40% or less, the formation of intermetallic compounds can be suppressed, so that a high resistivity can be maintained and excellent processability can be maintained. Therefore, the W content is preferably 40% or less. On the other hand, the lower limit of the W content is not particularly limited, but in order to obtain the effect of increasing the melting point and the effect of increasing the resistivity by using W, the W content is preferably 10% or more. The W content is more preferably 20% or more.

[0050] [The sum of the Mo content and the W content exceeds 30% and is less than 50%]

[0051] If the sum of the Mo content and the W content is less than 50%, no intermetallic compound of Mo or W is generated, or even if an intermetallic compound of Mo or W is generated, the amount is very small or disappears by heating. As a result, the effect of increasing the melting point and the effect of increasing the resistivity by Mo and W can be obtained, and excellent workability can be obtained. Therefore, the sum of the Mo content and the W content is set to less than 50%. The sum of the Mo content and the W content is preferably 47% or less. In addition, Mo and W can be solid-dissolved in Ru in a total of 40%. In order to suppress the decrease in resistivity and the decrease in workability caused by the formation of intermetallic compounds, the sum of the Mo content and the W content is more preferably less than 40%. The sum of the Mo content and the W content is 30% or more. The sum of the Mo content and the W content can be 33% or more.

[0052] [Ru-Mo-W alloy]

[0053] Impurities may be mixed into the Ru-Mo-W alloy in the composition due to the conditions of the manufacturing equipment and the manufacturing process. Impurities are elements mixed into the raw materials or mixed into the manufacturing process, and examples thereof include: light elements such as H, Li, B, C, N, O, S, Na, Mg contained in the crucible; transition metals such as Fe, Ni, Cu, Pb; rare earth elements, lanthanides, and actinides. The lower the impurity content, the better, and it can be 0%.

[0054] The Ru-Mo-W alloy may contain an element having a melting point of 1500°C or higher to replace a portion of Ru. Elements having a melting point of 1500°C or higher have a relatively low vapor pressure, so contamination of the furnace or the heated object caused by the element can be suppressed. Examples of elements having a melting point of 1500°C or higher include Fe, Ni, V, Pt, Ir, Rh, Al, C, and N.

[0055] Platinum group elements such as Pt, Ir or Rh have a high melting point and chemical stability, and also have a higher solubility than Ru. Therefore, the Ru-Mo-W alloy may contain platinum group elements.

[0056] In addition, since typical elements such as Al, C, or N do not form compounds with Ru, even if these elements are contained, the resistivity can be maintained at a high level. Therefore, the Ru-Mo-W alloy may contain the typical elements.

[0057] As described above, the element having a melting point of 1500°C or higher may be contained within a content range that allows the solidus temperature of the Ru—Mo—W alloy to be 1600°C or higher.

[0058] The chemical composition of the Ru—Mo—W alloy can be measured by the following method, that is, using a wavelength dispersive X-ray spectrometer (WDS) or an energy dispersive X-ray spectrometer (EDS).

[0059] The composition involved in this embodiment may be composed of only Ru-Mo-W alloy, or may contain other constituent materials. The composition may be, for example, a paste. In detail, the composition involved in this embodiment may be a mixture of powdered Ru-Mo-W alloy and at least a solvent. The particle size of the powdered Ru-Mo-W alloy can be any size as long as it can be mixed with a solvent to form a paste-like composition. Regarding the solvent, it may be a solvent obtained by dissolving a resin in an organic solvent, as long as it is a solvent generally used to manufacture a paste containing metal powder.

[0060] The paste-like composition may contain a binder for adjusting performance from the viewpoint of dispersibility, viscosity, and the like.

[0061] The mixture may further contain particles of an insulating material. The particles of the insulating material may be a known material, for example, at least one of glass or an inorganic oxide. The content of the insulating material is not particularly limited, and may be any content, for example, may be 0.01 volume % or more, 0.1 volume % or more, or 1 volume % or less, or may be 99 volume % or less.

[0062] Furthermore, the composition according to the present embodiment may be in the form of a thin film or a laminated film.

[0063] Hereinafter, the composition according to one embodiment of the present invention has been described.

[0064] <Resistance Heating Body>

[0065] Next, the resistance heating element according to the embodiment of the present invention is described. The resistance heating element according to the embodiment contains a Ru-Mo-W alloy, and the chemical composition of the Ru-Mo-W alloy is as follows: Mo is more than 0% and less than 49%, W is more than 0% and less than 45%, and the sum of the Mo content and the W content is more than 0% and less than 50%. More preferably, it is more than 10% and less than 50%, and even more preferably, it is more than 30% and less than 50%.

[0066] (shape)

[0067] The shape of the resistance heating body involved in the present embodiment is not particularly limited, and can be made into various shapes such as linear, rod-shaped, plate-shaped, block-shaped, or these appropriately processed shapes. In the manufacturing method using the following micro-pull-down method, it can be made into a linear shape, so the shape of the preferred resistance heating body is linear. It should be noted that the linear shape mentioned here refers to a shape with a diameter or a circle equivalent diameter of less than 3mm and extending in one direction, and the rod-shaped shape refers to a shape with a diameter or a circle equivalent diameter exceeding 50mm and extending in one direction.

[0068] (Metallic Structure)

[0069] Existing metal resistance heaters are formed through mechanical processing such as forging and wire drawing, and are therefore polycrystalline. Such metal resistance heaters (hereinafter, metal resistance heaters are sometimes referred to as metal resistance heaters) will undergo recrystallization during the heating cycle, and the resistivity and mechanical strength will change over time. As a result, the application conditions of the current and voltage used to raise the temperature to an arbitrary temperature may sometimes change. In addition, the mechanical strength may be reduced, causing the resistance heater to deform, resulting in accidental contact with surrounding components or disconnection. In addition, during the use of metal resistance heaters, nodal structures are often formed due to recrystallization or grain growth. Sometimes the electrical properties or mechanical properties may deteriorate due to the nodal structure, leading to disconnection.

[0070] (Elongation at break)

[0071] The elongation at break of the resistance heating body in the uniaxial tensile test at room temperature is preferably 5% or more, more preferably 70% or more, and further preferably 80% or more. The short-axis tensile test is performed in accordance with JIS Z2241:2011 or ASTM A370. However, in the case where a test piece that meets the standard cannot be obtained from the resistance heating body, a test piece in which the ratio of the distance between the markings to the maximum value in the width direction between the markings is 3 or more can be used.

[0072] When the resistance heating body involved in the present embodiment is a wire, its diameter is not particularly limited, and can be set to 0.1 mm or more and 3 mm or less, for example. However, this diameter is only for illustration and can be set to various diameters. In the following micro-pull-down method, for example, it can be set to 2 mm or less.

[0073] The resistance heating element according to the embodiment of the present invention has been described above.

[0074] <Manufacturing method>

[0075] The above-mentioned composition and the method for manufacturing the resistance heating element are not particularly limited, and can be manufactured, for example, by the following method. As an example, the method for manufacturing the wire of the resistance heating element is given below for explanation. The wire of the resistance heating element can be manufactured by a micro-pull-down method (hereinafter referred to as the micro-pull-down method μ-PD method). In the μ-PD method, Figure 3 , Figure 4 As shown, the molten metal 103 as a raw material is placed in a crucible 102 that can be heated by a high-frequency induction coil 101, and the solidified metal (wire) 105 is pulled down through a nozzle 106 via a culture crystal 104 to culture the crystal. The nozzle 106 is set at the bottom 107 of the crucible 102. The crucible 102 is supported and fixed on a crucible stand 109 inside a processing chamber 108. It should be noted that Figure 4 Yes means Figure 3 The enlarged view within the dotted circle.

[0076] As described above, the resistance heating element involved in this embodiment has a high melting point, so in the method for manufacturing a wire based on the μ-PD method, a material that is difficult to dissolve and volatilize at high temperatures can be used as the constituent material of the crucible 102. Specifically, the constituent material of the crucible 102 can be ceramics such as magnesium oxide, zirconium oxide, and aluminum oxide, or carbon (graphite), etc.

[0077] The nozzle 106 provided at the bottom 107 of the crucible 102 has both the function of cooling and solidifying the molten metal 103 passing through the bottom 107 and the function of constraining and molding the solidified metal (wire) 105 as a fixture (mold). The constituent material of the nozzle 106 is preferably formed of a material that is difficult to dissolve and volatilize at high temperatures, similarly to the crucible 102. Since the inner wall of the nozzle 106 will rub against the solidified metal, the inner wall surface of the nozzle 106 is preferably smooth.

[0078] The length of the nozzle 106 is not particularly limited. In order to solidify the molten metal 103 in the nozzle 106 and obtain a wire of a desired diameter, the length is preferably 3 mm to 30 mm. If the length of the nozzle 106 is too short, the solidification of the molten metal 103 in the nozzle 106 is insufficient. When the insufficiently solidified wire 105 is discharged from the nozzle 106, the solidification of the wire 105 is completed after the restraint of the nozzle 106 is released, so the wire 105 may expand and its wire diameter becomes thicker. On the other hand, if the length of the nozzle 106 is too long, the distance that the wire solidified in the nozzle 106 moves in the nozzle 106 becomes longer, and the pull-down resistance of the wire 105 becomes greater. As a result, the nozzle 106 may sometimes be worn or damaged, and it becomes difficult to control the shape and size of the wire.

[0079] In order to manufacture a wire of a desired shape and diameter, it is important to control the state of the molten metal 103 and the wire 105 in the nozzle 106. In detail, it is preferred that the position of the solid-liquid interface 111 is located near the center of the length direction of the nozzle 106. If the position of the solid-liquid interface 111 is located on the upper side (the crucible 102 side), the distance that the wire solidified in the nozzle 106 moves in the nozzle 106 becomes longer, and the pull-down resistance of the wire 105 becomes larger. As a result, the nozzle 106 may be worn or damaged, and it becomes difficult to control the shape and size of the wire. On the other hand, if the solid-liquid interface 111 is located on the lower side (the outlet side of the nozzle 106), the solidification of the molten metal 103 in the nozzle 106 becomes insufficient. When the insufficiently solidified wire 105 is discharged from the nozzle 106, the solidification of the wire 105 is completed after the restraint based on the nozzle 106 is released, so the wire 105 may expand and its wire diameter becomes thicker. The position of the solid-liquid interface 111 is controlled by appropriately adjusting the pull-down speed. The pulling speed is preferably set to 0.5 mm / min to 200 mm / min. The pulling speed can be adjusted by changing the winding speed of the wire 105 discharged from the nozzle 106 by a winding device (not shown).

[0080] The wire 105 discharged from the nozzle 106 is preferably slowly cooled in a temperature range exceeding the recrystallization temperature. If the wire 105 is rapidly cooled in a temperature range exceeding the recrystallization temperature, fine crystals may sometimes be produced. A resistance heating body having fine crystals may sometimes undergo recrystallization, and the resistivity and mechanical strength may change as the number of uses increases. Therefore, in order to prevent the occurrence of fine crystals, it is preferred to slowly cool the wire 105 in a temperature range exceeding the recrystallization temperature. At least in the case of manufacturing a resistance heating body having the above-mentioned chemical composition, it is preferred to slowly cool in a temperature range exceeding 1200°C.

[0081] The temperature range below the recrystallization temperature is not particularly limited, and rapid cooling may be performed within a temperature range of 1000° C. or below.

[0082] There is no particular limitation on the cooling rate. For example, a post heater (not shown) made of a thermally conductive material such as ceramic may be connected to the crucible 102 at the bottom of the crucible 102 to utilize the heat of the crucible 102 (molten metal 103).

[0083] The processing of the molten metal 103 in the crucible 102 and the pulling down of the wire 105 are preferably performed in an inert gas atmosphere to prevent oxidation. The inert gas may be, for example, nitrogen, argon, or helium.

[0084] For the wire 105 after cooling, the wire diameter can be adjusted by additional processing. However, when adjusting the linear shape, it is preferably processed in a way that no residual strain remains. When the processing temperature is low or the processing rate is high, the strain is sometimes left, and when used at high temperature, the structure changes due to recrystallization.

[0085] In the μ-PD method, since crystal growth is performed while the cross-sectional area is limited to a small area by the nozzle 106, the number density of grains having an orientation difference of 15° or more with adjacent grains in the cross section perpendicular to the length direction can be less than 200 grains / mm. 2 In addition, according to the μ-PD method, a wire of a desired size can be obtained without subsequent processing or with a smaller number of processing times.

[0086] The rod material of the resistance heating body can be manufactured by a known method, not limited to the μ-PD method. For example, a floating zone (FZ) method or a zone melting method can be applied. In addition, according to the floating zone method and the zone melting method, a resistance heating body of a larger size can be manufactured compared to the μ-PD method.

[0087] The preparation of the Ru-Mo-W alloy powder constituting the composition is not particularly limited, and can be prepared, for example, by pulverizing the resistance heating element prepared by the above method using a known method. In addition, a known method for preparing metal powders such as an atomization method can be applied.

[0088] The composition including the Ru—Mo—W alloy powder can be produced by mixing the powder with a solvent, or a solvent and an insulating material powder, by a known method.

[0089] In addition, the thin film composition can be produced by, for example, physical vapor deposition (PVD), chemical vapor deposition (CVD), arc ion plating (AIP), or the like.

[0090] The composition and the resistance heating element according to the embodiment of the present invention have been described above. However, the technical scope of the present invention is not limited to the above-described embodiment, and various modifications can be made without departing from the gist of the present invention.

[0091] As further described in detail in the following examples, the compositions and resistance heaters according to the embodiments of the present invention are excellent in durability, resistivity, temperature dependence of resistivity, and processability at room temperature. Therefore, the compositions and resistance heaters according to the embodiments of the present invention can be applied to various heating devices. The compositions and resistance heaters according to the embodiments of the present invention can be applied to, for example: a baking furnace for baking ceramics, magnets, or capacitors; a HIP (hot isostatic press) device or hot pressing device for manufacturing sputtering targets or diffusion bonding of dissimilar materials; a heat treatment furnace for removing internal defects of metals; a single crystal manufacturing device for growing single crystals; a heater for heating a substrate in a film forming device, or a filament or boat of a vapor deposition device.

[0092] Example

[0093] Next, an embodiment of the present invention is shown. The conditions in the embodiment are a conditional example adopted to confirm the feasibility and effect of the present invention. The present invention is not limited to the conditions used in the following embodiments. The present invention can adopt various conditions as long as the purpose of the present invention can be achieved without departing from the main purpose of the present invention.

[0094] <Example 1>

[0095] The resistivity of Ru-Mo alloy wires prepared with various Mo contents, Ru-W alloy wires prepared with various W contents, and Ru-Mo-W alloy wires prepared with various Mo contents and W contents were measured. Figure 3 , Figure 4 The manufacturing device described in the invention manufactures wires of Ru-Mo-W alloy, Ru-Mo alloy and Ru-W alloy with different chemical compositions by μ-PD method. Specifically, the raw metal is placed in a zirconia crucible (container size 40 mm×30 mm×50 mm). In addition, the culture crystal ( In this state, the raw material is melted by high-frequency induction heating using a high-frequency induction coil.

[0096] After the raw material molten metal was formed in the crucible, the molten metal was pulled down at a pulling speed of 100 mm / min to produce a wire material having a wire diameter of 1 mm and a length of 5000 mm.

[0097] The chemical composition of each Ru-Mo-W alloy prepared is Ru 0.60 Mo 0.10 W 0.30 、Ru 0.60 Mo 0.20 W 0.20 、Ru 0.70 Mo 0.10 W 0.20 、Ru 0.70 Mo 0.15 W 0.15 、Ru 0.70 Mo 0.20 W 0.10 And Ru 0.90 Mo 0.05 W 0.05 .

[0098] The resistivity was measured at room temperature by a four-terminal method.

[0099] Figure 2 A graph showing the relationship between the Mo content and the W content relative to Ru and the resistivity is shown. Figure 2 As shown in the figure, when the Mo content in the Ru-Mo alloy and the W content in the Ru-W alloy are respectively less than 40 atomic %, the resistivity increases with the increase of the Mo content and the W content.

[0100] Figure 1 The resistivity of the Ru-Mo-W alloy at 25°C is shown. Figure 1 This graph was created based on the actual measured values ​​using Origin 2022, a graphics software produced by OriginLab Corporation. Figure 1 The plots in are measured values. Figure 1 As shown in the figure, it is found that the resistivity increases by making Ru contain at least one of Mo and W.

[0101] <Example 2>

[0102] The chemical composition was changed and a wire of Ru-Mo-W alloy was prepared in the same manner as in Example 1 to study the temperature dependence of resistivity. 0.65 Mo 0.15 W 0.25 And Ru 0.60 Mo 0.20 W 0.20 The resistivity of each sample at each temperature was measured by pulse current heating method. Figure 5 A graph showing the temperature dependence of resistivity is shown. Figure 5 Graph 2 shows the temperature dependence of the resistivity of Ta as a comparative example.

[0103] The temperature control in a resistance heating furnace is usually achieved by measuring the temperature in the furnace using a temperature measuring instrument such as a thermocouple, and controlling the voltage and current applied to the resistance heating body in such a way that the obtained temperature in the furnace is close to the target temperature. Therefore, it is expected that the rate of change of the resistivity of the resistance heating body relative to the temperature change is smaller. It is known that the resistivity of metals increases approximately linearly with temperature, but the proportionality coefficient varies from metal to metal. In addition, the temperature dependence of the resistivity often becomes nonlinear due to the influence of the anharmonic vibration of phonons.

[0104] like Figure 5 As shown in FIG. 1 , in a temperature range exceeding 1800°C, the resistivity of the Ru-Mo-W alloy is about the same as that of Ta, but in a temperature range below 1800°C, the resistivity of the Ru-Mo-W alloy becomes greater than that of Ta. Therefore, in a temperature range below 1800°C, the heating efficiency of the Ru-Mo-W alloy is greater than that of Ta, so the heating rate becomes faster. For example, the melting point of LiF, one of the evaporation raw materials of organic EL, is 848.2°C, and the operating temperature of the resistance heating body in the evaporation of LiF is below 1300°C. Therefore, the Ru-Mo-W alloy is also useful for the evaporation of organic EL raw materials such as LiF.

[0105] In addition, if Figure 5 As shown in FIG. 1 , the inclination of the resistivity graph of the Ru-Mo-W alloy is smaller than that of the resistivity graph of Ta. That is, since the temperature dependence of the resistivity of the Ru-Mo-W alloy is smaller than that of the Ta, the Ru-Mo-W alloy can achieve higher controllability of the furnace temperature than Ta.

[0106] <Example 3>

[0107] The Ru-Mo-W alloy was prepared in the same manner as in Example 1, and the emissivity at various temperatures was measured. The chemical composition of the Ru-Mo-W alloy is Ru 0.65 Mo 0.15 W 0.25 The emissivity of each sample at each temperature was measured by pulse current heating method. Figure 6 A graph showing the temperature dependence of emissivity is shown. Figure 6 Graph 1 shows the temperature dependence of the resistivity of Ta, W, and Mo as comparative examples.

[0108] Next, consider the case where a resistance heating element is used as a heater for radiation heating.

[0109] The resistance heater generates light energy by radiation according to temperature. When the resistance heater is used as a heater for vapor deposition of organic EL materials, radiation becomes the main heat conduction mechanism because it is used in a high vacuum state. In this case, according to the Stefan-Boltzmann law expressed by the following formula (1), the heated object is heated by the radiation energy I.

[0110] I=εσT 4 ...(1)

[0111] Here, in the above formula (1), ε is the emissivity (Wm -2 ), σ is the Stefan Boltzmann constant (Wm -2 K -4 ), T is the temperature (K). Since the intensity of the radiant energy emitted from the resistance heating body is proportional to the emissivity, the higher the emissivity, the higher the thermal conductivity.

[0112] like Figure 6 As shown in the figure, the emissivity of the Ru-Mo-W alloy is the same as that of Ta, W and Mo above 1800°C, but is higher than that of Ta, Mo and W in the temperature range below 1800°C, and the difference becomes larger as the temperature decreases. Therefore, in the temperature range below 1800°C, the current consumption of the Ru-Mo-W alloy can be made smaller than that of the Ta wire, and therefore, in the temperature range below 1800°C, the power consumption of the Ru-Mo-W alloy becomes smaller than that of the Ta wire. Furthermore, since the Ru-Mo-W alloy has high thermal conductivity, it responds faster to the temperature rise caused by the application of voltage. Therefore, when the Ru-Mo-W alloy is used in the evaporation of the organic EL material, the time for the evaporation speed to reach stability (stabilization time) is shorter than the stabilization time when the Ta wire is used.

[0113] <Example 4>

[0114] The Ru 0.60 Mo0.15 W 0.25 (Samples R-2, R-3) and Ru 0.60 Mo 0.20 W 0.20 The wire of Ru-Mo-W alloy (sample R-4) and the wire of Ru (R-1) were prepared and the metal structure was observed and the room temperature tensile test was performed. Samples R-1, R-3 and R-4 were prepared by the same method as in Example 1. In the preparation of samples R-2 and R-3, seed crystals with different numbers of crystal grains were used. Specifically, seed crystals with a large number of crystal grains were used in sample R-2.

[0115] The metal structure of each sample of R-1 to R-4 was observed by the electron backscatter diffraction (EBSD) method. Specifically, the cross section of the resistance heater perpendicular to the length direction was etched or ion milled, and the cross section after treatment was observed in a field of view with a magnification of 30 to 300 times using a scanning electron microscope (SEM), and the grains and crystal orientation were identified using the electron backscatter diffraction method. In the EBSD method, the grain boundary with an orientation difference of more than 15° between adjacent grains is defined as a high-angle grain boundary, and the particles separated by the high-angle grain boundary are defined as one grain. Figure 7 The analysis results obtained by the EBSD method are shown.

[0116] A room temperature tensile test was performed on each of the prepared samples to produce a stress-strain curve. The room temperature tensile test was performed in accordance with JIS Z2241:2011. Figure 8 The stress-strain curve of each sample is shown.

[0117] It is known that polycrystals of Ru and existing Ru alloys are difficult to process. If they are to be processed at room temperature, brittle fracture will occur due to grain boundary fracture. Therefore, it is extremely difficult or impossible to process polycrystals of Ru and existing Ru alloys at room temperature. As a method to improve the ductility of Ru and Ru alloys, it is effective to reduce the grain boundary density by alloying and single crystallization or unidirectional solidification organization.

[0118] Regarding alloying, even if W is added to Ru, ductility cannot be improved, and brittle fracture occurs at room temperature. On the other hand, Mo has the effect of imparting ductility to Ru.

[0119] Regarding the use of single crystal or unidirectional solidification organization to reduce the grain boundary density, the reduction of Ru grain boundary density can greatly improve ductility. According to non-patent literature 2-3, the elongation at break of Ru manufactured by powder metallurgy is about 0% to 3%, and almost no ductility is shown. It is usually possible to reduce the grain boundary density in single substances and alloys by crystal growth methods. For techniques that can be applied to Ru alloys, the existing known Czochralski method, Bridgman method, Floating zone method, and μ-PD method and other crystal growth methods can be applied. In particular, the μ-PD method can accurately control the shape. In addition, since it can continuously manufacture tens of meters long wires, it is ideal as a net shape (Net-Shape) forming method for resistive heating elements.

[0120] like Figure 7 As shown in Figure 1, the EBSD results show that samples R-1, R-3 and R-4 are single crystals or polycrystalline with very few grains, and R-2 is polycrystalline. Figure 8 As shown, R-1 can obtain an elongation at break of about 80%, and R-2 can obtain an elongation at break of about 70%, both of which are greater than the elongation at break of R-4. On the other hand, the elongation at break of R-3 is less than that of R-4. In addition, the elongations at break of R-2 and R-3 are significantly greater than the elongations at break of existing Ru alloys (0% to 3%). Therefore, it can be seen that the Ru-Mo-W alloy manufactured by the μ-PD method exhibits greater ductility.

[0121] Explanation of symbols

[0122] 101 High frequency induction coil

[0123] 102 Crucible

[0124] 103 Molten Metal

[0125] 104 Cultivating Crystals

[0126] 105 Solidified metal (wire)

[0127] 106 Nozzle

[0128] 107 bottom

[0129] 108 Processing Room

[0130] 109 Crucible Table

[0131] 111 Solid-Liquid Interface

Claims

1. A composition, characterized in that The composition contains a Ru-Mo-W alloy, and the chemical composition of the Ru-Mo-W alloy is calculated in atomic % as follows: Mo: more than 0% and less than 49%, W: more than 0% and less than 45%, The sum of the Mo content and the W content exceeds 30% and is less than 50%.

2. The composition according to claim 1, wherein The chemical composition of the Ru-Mo-W alloy contains, in atomic %,: Mo: 10% or more and 40% or less, W: 10% or more and 40% or less, The total of the Mo content and the W content in the Ru—Mo—W alloy is 20% or more and 47% or less.

3. The composition according to claim 1 or 2, wherein The Ru—Mo—W alloy is in powder form or at least in paste form mixed with a solvent.

4. The composition according to claim 1 or 2, wherein The composition including the Ru—Mo—W alloy is a thin film.

5. A resistance heating element, characterized in that: The resistance heating body contains a Ru-Mo-W alloy, and the chemical composition of the Ru-Mo-W alloy is calculated in atomic % as follows: Mo: more than 0% and less than 49%, W: more than 0% and less than 45%, The sum of the Mo content and the W content is less than 50%.

6. The resistance heating element according to claim 5, wherein: The chemical composition of the Ru-Mo-W alloy contains, in atomic %,: Mo: 10% or more and 40% or less, W: 10% or more and 40% or less, The total of the Mo content and the W content in the Ru—Mo—W alloy is 20% or more and 47% or less.

7. The resistance heating element according to claim 5 or 6, wherein: The elongation at break in a uniaxial tensile test at room temperature is 5% or more.

8. The resistance heating element according to claim 7, wherein: The resistance heating body is in the shape of a wire or a rod.

Citation Information

Patent Citations

  • Method for manufacturing highly heat resistant conductive thin film, highly heat resistant conductive thin film and laminated film obtained by the manufacturing method, and device provided with the laminated film

    JP2005281767A

  • Analogue input unit and method for controlling the same

    JP2022134489A